Significados e vivências dos pais e responsáveis sobre o filho usúario de crack e outras drogas: uma abordagem fenomenológica - Bruno David Henriques (2014)
The restructuringprocess of the mental healthpolicyaims tostrengthencommunity-basedmodels, guided by the principlesof psychiatric reform.This movementaims toimprove thequality of assistance, as well as facilitating accessof the populationthat needsfollow-up, includingthe approachtoalcohol users, crack and other drugsregarding theprevention, treatmentand rehabilitation. This isapublic health problemwith largemagnitudeandseveral issues involved. Consumption of illegaldrugshas increasedinall segments of society, especially amongchildren andadolescents,impactingonindividual and family, immeasurably. In this context, the study aimed to understandthe parents experienceson thechild userof crack andother drugs. This isa qualitative research, with phenomenologyas stream ofanalysis. Interviews were conducted with parents and guardians of children and adolescents users of crack and other drugs monitored in the Reference Center on Children's Mental Health ( CERSAMi ) in the city of Belo Horizonte, Minas Gerais . After signing the informed consent, the interviews were recorded and guided by the following question: "How is for you having a son who is a drug user?". The saturation criterion was used to determine the number of participants and the end of the collection. This moment was characterized by the repetition of speeches, fact occurred in the 11th interview. The testimonials were analyzed based on three moments proposed by Martins and Bicudo, 1989: description, reduction and phenomenological understanding. Initially, after an exhausting reading of the meaning units,it was possible the development of nineteen subjects of analysis which converged to the construction of three categories of analysis that expose the phenomenon related to the meaning given by parents to drug use by their son.1) perceptions and criticisms to the actions of public power in confronting the use/abuse of drugs. 2) feelings and perceptions of family regarding the support, care and treatment network. 3) understanding the repercussion of drug use by children and adolescents inside of the families. The research allowed to increase the knowledge about the meanings and the difficulties faced by families who have a son (child or adolescent) user of crack and other drugs, besides providing funding for planning, implementing and improving the quality of services assistance that perform individual and collective attendance.